Bridging conceptual gaps for smooth teaching and learning - Adhikari, Haris C. (Journal of NELTA, 2019)
This paper primarily aims to reflect on the majority of my students’ inadequacies of using ‘remembering’, ‘understanding’, ‘analyzing’ and ‘evaluating’, four major levels of the Revised Bloom’s Taxonomy (2001), a helpful reading and writing technique included in Kathmandu University’s first year first semester undergraduate compulsory English and professional communication course, of course for the benefit of all the concerned ones—especially for those from the Asian regions whose communication in English reveals a number of linguistic and technical problems. The focus is more on the level of analysis, because the students had more problems regarding this level. My purpose is to make the level of analysis simpler, more systematic and practical, outlining its nature and various forms, and the inadequacies involved on the part of(the) students, analyzing alongside an analysis part of an assignment submitted by one of my students and a short, well known-about text taken from elsewhere. In doing so, I resort to certain assumptions of a body of theories, namely that of social support theory, reader response theory, and Gestalt theory, apart from my (experimental) experiences of teaching the Taxonomy. These assumptions and experiences gave me insights into how contextually analytical responses are safer when compared to shallow critical responses. I found that shorter texts are more helpful in introducing students to the Taxonomy. I also came across realizations about the importance of balance between textual contexts and extensions of mind, about the effectiveness and beauty of heuristic as well as holistic approaches with emphasis on bridging upon the basic conceptual gaps because of which inadequacies and difficulties arise.